ACCELERATION OF THE DECREASE OF STUNTING EVENTS THROUGH HEALTH PROMOTION MEDIA AT DESI MIDWIFE PMB CLINIC - Kartadarma, Supriyatni; Yusita, Intan; Rofiasari, Linda; Kaniawati, Marita; Valiani, Cici; Agustina, Agustina (Indonesian Journal of Community Development, 2021)
During this Pandemic, we must prevent the spread of Covid-19 but still pay attention to efforts to reduce morbidity and mortality in infants. The existence of the Covid-19 pandemic in Indonesia that affects health service activities, one of which is not holding the posyandu program, brings its own concerns for all sectors related to health policies, especially for parents who have infants under five in their growth and development period who require supervision. Based on data from the Bandung City Health Office in 2019, it was reported that there were 9 toddlers with malnutrition in Derwati Village.